2017
DOI: 10.1556/004.2017.052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperament on cortisol response to a single exercise bout in Thoroughbred racehorses – short communication

Abstract: Temperament has not been taken into account in previous studies evaluating the stress response to exercise in horses. The aim of the present study was to investigate the cortisol response in Thoroughbred racehorses to a single exercise bout, and to analyse the results based on the basic personality of the horse examined. Twenty healthy Thoroughbred horses were selected for the study based on a 25-item rating questionnaire survey used for characterising equine temperament. Eight temperamental and twelve calm ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…In the present study's measurement of HRV as a physiological parameter of autonomic stress levels including pain, significant changes were not observed in the SDNN or RMSSD after the dermal suctioning session (Figure 7). In humans, cupping therapy has been found to increase parasympathetic nervous system activity by inducing peripheral nerve stimulation (Arslan et al, 2014) Cortisol is a hormone secreted via the hypothalamuspituitary gland-adrenal cortex as a biological response to stress and is often used in horses to evaluate stress levels, including pain (Bohák et al, 2017;Bussières et al, 2008;Pritchett et al, 2003;Sellon et al, 2004). In the present study, cortisol concentrations did not change significantly after dermal suctioning (Figure 6).…”
Section: Please Cite This Article As 'In Press'mentioning
confidence: 43%
“…In the present study's measurement of HRV as a physiological parameter of autonomic stress levels including pain, significant changes were not observed in the SDNN or RMSSD after the dermal suctioning session (Figure 7). In humans, cupping therapy has been found to increase parasympathetic nervous system activity by inducing peripheral nerve stimulation (Arslan et al, 2014) Cortisol is a hormone secreted via the hypothalamuspituitary gland-adrenal cortex as a biological response to stress and is often used in horses to evaluate stress levels, including pain (Bohák et al, 2017;Bussières et al, 2008;Pritchett et al, 2003;Sellon et al, 2004). In the present study, cortisol concentrations did not change significantly after dermal suctioning (Figure 6).…”
Section: Please Cite This Article As 'In Press'mentioning
confidence: 43%
“…This is in agreement with the reports from other studies in cattle and horses. Bohak et al [45] investigated the influence of personality on the cortisol response when thoroughbred racehorses were exposed to exercise and found that horses with more excitable temperament had higher cortisol concentrations compared to those with less excitable temperament. The authors suggested that serum cortisol concentrations may be a good indicator of temperament levels in racehorses.…”
Section: Discussionmentioning
confidence: 99%